2016
DOI: 10.13080/z-a.2016.103.029
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of irrigation-drainage scheme for tomato crop based on multi-index analysis and projection pursuit model

Abstract: Various indexes should be considered when developing a suitable irrigation and drainage scheme for crops. Our study chosen tomato as plant material and conducted a field experiment under saline soils. Nine treatments distinguished by different irrigation quotas and different drain ditch depths were used for the optimization of irrigation-drainage scheme. A flooding irrigation treatment with no surface drainage was adopted as control. The system of evaluation indexes was established in comprehensive considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…The previous study by Zhai, Yang & Hou (2015) found that salt stress inhibited the growth of tomato fruit, thereby decreasing the weight of single fruit and the yield from a single plant. However, some studies revealed that slight salt stress improved the tomato quality and increased the concentration of nutrient in the fruit ( Hou & Shao, 2016 ; Wan et al, 2007 ). Even so, for those greenhouse soils subjected to strong evaporation and less water supply, the soil salinity was expected to be lower.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous study by Zhai, Yang & Hou (2015) found that salt stress inhibited the growth of tomato fruit, thereby decreasing the weight of single fruit and the yield from a single plant. However, some studies revealed that slight salt stress improved the tomato quality and increased the concentration of nutrient in the fruit ( Hou & Shao, 2016 ; Wan et al, 2007 ). Even so, for those greenhouse soils subjected to strong evaporation and less water supply, the soil salinity was expected to be lower.…”
Section: Discussionmentioning
confidence: 99%
“…The total sugar content was measured using the Fehling reagent titration method. The total acid content was measured using the sodium hydroxide titration method ( Hou & Shao, 2016 ). The SAR is calculated as the ratio of total sugar to total acid content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hou [70] adopted the projection pursuit model to select the best drip irrigation scheme for crop. Other methods, such as principal component analysis, entropy weight coefficient model were also used for guiding the agricultural production [71].…”
Section: Discussionmentioning
confidence: 99%
“…ET is calculated using the water balance equation of the farm land (Hou and Shao, 2016): eqnarrayleftET=P+I+U-R-D-ΔW where, P is the valid rainfall (mm), I is the irrigation amount (mm), U is the groundwater recharge (mm), R is the runoff (mm), D is the deep percolation (mm), and ΔW is the variation of soil moisture before and after the experiment (mm). For this study, P, U (the ground water level is below 9 m), R and D can be ignored.…”
Section: Methodsmentioning
confidence: 99%